A new electrochemical sensor for the simultaneous determination of guanine and adenine: using a NiAl-layered double hydroxide/graphene oxide-multi wall carbon nanotube modified glassy carbon electrode. Issue 92 (8th October 2015) - Rezaei, Behzad; Khosropour, Hossein; Ensafi, Ali Asghar; Dinari, Mohammad; Nabiyan, Afshin
<x xml:space="preserve">Abstract</x> An electrochemical sensor was developed for guanine and adenine detection using multiwall carbon nanotubes with the hybrid NiAl-layered double hydroxide/graphene oxide (NiAl-LDH/GO) on a glassy carbon electrode.